Reference rot degrades information preservation and induces the loss of intellectual integrity - Teixeira da Silva, Jaime A. (Epistēmēs Metron Logos, 2021)
The age of open access has ushered in a greater desire to cross-cite information from a multitude of sources, some of which may have a determined fate and life cycle. Information insecurity caused by the loss or transposition of information also negatively impacts information integrity by reducing its use and usefulness. Reference rot refers to the phenomenon in which the link to a web resource or journal article URL no longer function, revealing instead a “404 not found” error message. Reference rot can reduce the reliability and usefulness of a manuscript because access to information supporting claims and/or positions within a paper ceases to exist. Academic papers carry a complex mixture of information that is derived from a multitude of sources. Collectively, they ensure a paper’s health and functionality, aspects that fade as access to supporting information becomes truncated, i.e., reference rot, ultimately reducing the usefulness of the academic paper, and making it, and its claims, unreliable. Although it is a cumbersome task, as the curators of academic and scientific information, extant journals and their editors should revisit URLs in the reference lists regularly to update any broken links or URLs, and correct reference lists accordingly. This laborious task should involve close coordination between editors and authors to ensure, as best as possible, the sustained integrity of citations and thus the information backbone of a manuscript. An academic paper with a strong, or fortified, citation base, has greater information integrity, reliability and use for science and society.